International Connectivity and the Digital Divide in Sub-Saharan Africa - (:unkn) unknown (My University, 2020)
During the last decades, international connectivity has improved significantly with the worldwide deployment of some 400 fiber submarine cables (SMCs), transmitting more than 99% of international telecommunications. If sub-Saharan African (SSA) has long remained excluded from this interconnection process, the maritime infrastructure network has recently densified and spurred African connectivity catch-up. This paper estimates the impact of SMC deployment on the digital divide in an original sample of 49 SSA countries covering the period 1990-2014. Diff-in-diff (DID) estimations are conducted and highlight the particular contribution of SEACOM and EASSy cables, laid in 2009-2010, to Internet penetration in Eastern and Southern Africa. According to DID estimates these SMCs rollout has yielded a 3-5 percentage-point increase in internet penetration rates in this region compared to the rest of the continent. Triple-difference estimations emphasize conditional factors under which these cables have fostered Internet uptake: enlarged Internet bandwidth per users, lower broadband Internet tariffs, higher investment in the mobile network, improved terrestrial connectivity, and electricity access.
Keywords: African Research